Dissolved organic matter molecular composition data in two Arctic fjords, Scoresby Sund (Greenland) and Kongsfjorden (Svalbard) during MARIA S. MERIAN cruise MSM56 (MECAF) - Fabian Moye; Jana K Geuer; Claudia Burau; Mourad Harir; Philippe Schmitt-Kopplin; Boris P Koch; Tilmann Harder; Jan Tebben (PANGAEA, 2024)
Data presented here show the molecular composition of dissolved organic matter (DOM) as part of the MSM56 cruise (Project MECAF, Koch et al. (2019)). Water samples collected from different depths in Kongsfjorden (Svalbard), Fram Strait and Scoresby Sund (Greenland; July 2016; also see Friedrichs et al. (2017)) and were extracted with solid phase extraction following Dittmar et al. (2008). The molecular composition was obtained with Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) with negative electrospray ionization (ESI) on a Solarix 12 T (Bruker Daltonics GmbH, Germany) at the Helmholtz Munich, Research unit Analytical Biogeochemistry, Germany as described in Wünsch et al. (2018). A complementary data set was generated with Fourier-Transform Orbitrap mass spectrometry (FT-Orbitrap-MS) with negative ESI on a Q-Exactive Plus (Thermo Fisher Scientific, Bremen, Germany) at the University of Bremen, Marine Chemistry Group. A small number of samples were insufficient for analysis on both platforms and were measured by FT-ICR-MS only. Molecular formulas were assigned with the Ultra Mass Explorer (UME, www.awi.de/en/ume, Leefmann et al. (2019)). A mixing experiment was conducted between marine and runoff DOM samples and subsequentially measured with FT-Orbitrap-MS. The data set contains the raw peak list as well as the filtered molecular formulas.